Use of the Rumination Profile Through Collar Sensors for Mastitis Diagnosis in Dairy Cows - Schmidt, Ana Paula; Vieira, Laura Valadão; Barbosa, Antônio Amaral; Marins, Leonardo; Corrêa, Marcio Nunes; Del Pino, Francisco Augusto Burkert; Brauner, Cássio Cassal; Rabassa, Viviane Rohrig; Feijó, Josiane de Oliveira; Schmitt, Eduardo (Acta Scientiae Veterinariae, 2021)
Background: Mastitis is an inflammatory disease of the mammary gland, mostly associated with bacterial infections. It is responsible for great economic losses due to decreased milk yield, discarded milk, milk composition alterations and treatment costs, besides it impairs the animal health and welfare. The rumination time is an important behavioral marker and its assessment can be used as an early diagnosis tool, which can improve cure rate. Therefore, the aim of the present study was to evaluate the sensitivity of behavior monitoring system collars in the diagnosis of mastitis and the average rumination time (RT) of Holstein cows during the healthy period and affected by the disease. Materials, Methods & Results: The study was conducted on a commercial property located in the municipality of Rio Grande, Rio Grande do Sul, Brazil. The RT data from 39 multiparous Holstein cows with an average milk yield of 38.4 L/day was collected. RT monitoring was performed using C-Tech1 collars combined with CowMed® software, which assess behavior data from the animals and emits warning signals when it finds abnormalities in any parameter. In order to verify whether the animals were determined correlated with diseases, the sensitivity of the data was evaluated, when the system had given the alert to animals considered ill, they underwent to a further clinical evaluation performed by a veterinarian to confirm the diagnosis. From the diagnosis, the cows were divided into subclinical mastitis (SM) and clinical mastitis (CM) groups. SM was detected by the Californian Mastitis Test (CMT) and cows that were graded 1 (++), 2 (++) or 3 (+++) without the presence of any other clinical sign were assigned to the SM group. CM was assessed by observation of abnormalities in milk such as changes in color and consistency, as well as the presence of lumps, clots or blood; and clinical examination of the udder was performed for detection of hot, hard, swollen or painful quarters. Thereafter, variations in the mean RT between the healthy (15 days) and sick periods (days when there was an alert) were evaluated. For the identification of the etiological agents involved in the cases of CM, microbiological cultures were performed on Accumast® plates with milk samples, which were incubated at a temperature of 37°C and the diagnosis of the pathogens were performed after16 h of incubation. During the study, 57 cases of mastitis were observed, 42 were SM and 15 were CM. The sensitivity of the system, which is the ability to detect positive cases of the disease, was 73.8% for SM and 73.3% for MC. The RT of the animals were compared individually during the healthy period with the sick period and it was observed that SM reduced the RT by 5.33% whereas MC reduced the RT by 14.9%. Discussion: The maximum RT values were lower during the disease period in relation to the period in which the animals were healthy, for both SM and CM, which is due to the fact that the disease is responsible for causing inappetence in animals, among other clinical signs, therefore, reducing feed consumption. The lowest variation in RT, between the healthy and sick period, was observed in cases of SM, which was already expected, since the clinical form tends to cause more discomfort to the animals. As for the main etiological agents involved in the clinical condition, Streptococcus agalactiae and S. uberis were detected. In view of the above, the evaluation of the mean RT of multiparous dairy cows was efficient in the predictive diagnosis of SM and CM up to 2 days before the onset of the disease. In addition, the variability of this result demonstrated that animals with subclinical cases presented less fluctuation in RT.